Implementation of self-tuning controllers - Warwick, Kevin 1954- (London P. Peregrinus on behalf of the Institution of Electrical Engineers, 1988)
The first chapter of this book not only provides an overview of the scope and generality provided by self-tuning control schemes, but also indicates where such a scheme might be of benefit and how it complements and augments other control techniques. Chapters 2-5 discuss the basic ideas behind self-tuning control techniques; identification/ parameter estimation (chapter 2), optimal controller design (chapter 3), numerical considerations (chapter 4) and simplified methods (chapter 5). Chapters 6-9 discuss advances in the framework employed for self-tuning control; the delta operator (chapter 6), continuous-time control (chapter 7), software aspects (chapter 8) and predictive control (chapter 9). Chapters 10-13 are concerned with detailed application examples of; predictive control (chapter 10), PIP control (chapter 11), LQG optimal control (chapter 12) and various SISO/MIMO case studies (chapter 13).
Electronic reproduction.
Keywords: Self-tuning controllers; Electronic books